2020
DOI: 10.1186/s12931-020-01473-2
|View full text |Cite
|
Sign up to set email alerts
|

Laryngopharyngeal reflux in chronic obstructive pulmonary disease - a multi-centre study

Abstract: Reflux of gastric content has been associated with recurrent exacerbations of chronic obstructive pulmonary disease (COPD). We aimed to assess the prevalence of laryngopharyngeal reflux (LPR) in COPD and if LPR is a contributing factor to clinically relevant outcomes in COPD. We evaluated a total of 193 COPD patients (GOLD I-IV) with a 24-h laryngo-pharyngeal pΗ-monitor. LPR was observed in 65.8% of COPD patients and it was not significantly associated with clinically relevant outcomes of COPD. Treatment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Several potential mechanisms may explain the increased risk of COPD associated with GERD. First, GERD reflux can lead to chemical or aspirational pneumonia (Sanchez et al, 2020), which can further promote the occurrence and progression of COPD (Hu et al, 2015). Studies have found that controlling GERD with proton pump inhibitors significantly reduces the risk of exacerbations in COPD (Kang et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Several potential mechanisms may explain the increased risk of COPD associated with GERD. First, GERD reflux can lead to chemical or aspirational pneumonia (Sanchez et al, 2020), which can further promote the occurrence and progression of COPD (Hu et al, 2015). Studies have found that controlling GERD with proton pump inhibitors significantly reduces the risk of exacerbations in COPD (Kang et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of COPD patients having a common cough, GERD is associated with COPD and is considered a co-morbidity 77 . In fact, GERD has been observed to be a predictor of exacerbations in COPD and implies that a higher prevalence of these bacteria could be used as a potential indicator of COPD exacerbations 77 , 78 .…”
Section: Discussionmentioning
confidence: 99%
“…The more severe the degree of COPD, the more prominent gastrointestinal symptoms. 18,19 The reflux was caused by the incompetence of the lower oesophagal sphincter (LES). Reflux can occur through 3 mechanisms: spontaneous reflux during LES relaxation, backflow of gastric content during the swallowing process, and increase of abdominal pressure.…”
Section: Pathomechanism Of Gerd and Lung Diseasementioning
confidence: 99%